К определению магнитного поля контура с током над плоской поверхностью идеально проводящего тела - Васецкий, Ю.М.; Власов Д.И. (Технічна електродинаміка, 2012)
On the basis of the formulated boundary problem of magnetic field calculation the decision in the form of a field of initial current contour and its mirror medium boundary reflection is presented. It is shown, that at correct formulation of the problem when the initial contour is closed, the necessary condition of continuity of surface density current is satisfied.